Duality of O(N) and Sp(N) random tensor models: tensors with symmetries - Keppler, Hannes; Krajewski, T.; Muller, T.; Tanasa, A. (Journal of physics. A, Mathematical and theoretical, 2023)
In a recent series of papers, a duality between orthogonal and symplectic random tensor models has been proven, first for quartic models and then for models with interactions of arbitrary order. However, the tensor models considered so far in the literature had no symmetry under permutation of the indices. In this paper, we generalize these results for tensors models with interactions of arbitrary order which further have non-trivial symmetry under the permutation of the indices. Totally symmetric and anti-symmetric tensors are thus treated as a particular case of our result.